Bhumij of Naranpur: A study visualising the lesions from history - Malik, Sebati (Third Concept)
The present paper is about the imitation of research in the field of social sciences. The ambitious efforts of the early scholars to instigate the life of the indigenous population had become successful. Their bravery in venturing into inhospitable deep forest, uninhabited beaches and accoutering individuals who are unable to comprehend the reasons of their visit is respected.
Keywords: Bhumij of Naranpur, Indigenous Communities, Social Science Research, Ethnographic Study, Historical Inquiry, Tribal Life, Early Scholars, Fieldwork Challenges, Cultural Documentation, Research Methodology, Indigenous Histories, Anthropological Exploration